The role of congruence between vernacular built environments and tradition as an integral part of design for enhancing the quality of life - GhaffarianHoseini, AmirHosein; Ibrahim, Rahinah; Baharuddin, Mohd Nasir (2010)
The congruency between residential functional spaces and tradition is perceived as an integral part of design for enhancing the quality of life. However, the quality of contemporary residential functional spaces is mostly based on style and modernity rather than the tradition of that particular regional context. In view of the rapid modernization of Malaysia, the kampong house as the Malay vernacular built environment has been replaced by modern residential design. Thus, several aspects of kampong which identified it as a major vernacular value, has been lost inside contemporary functional spaces. On the other hand, nowadays the modern architecture with its stylish features has been promoted in new towns without any concern to the idea of vernacular architecture. However many Malay inhabitants still prefer to live in houses which are based on their own tradition of regional context. This is because the quality of housing as one of the influential factors in enhancing the quality of life of the users is not based on their cultural values. This research would like to study the Malay kampong houses as the Malay vernacular built environment. In this research, the vernacular architectural features of kampong houses representing Malay vernacular houses are studied using archival search. We use text analysis for analyzing the cultural meanings of vernacular functional spaces and their functional spatial features. Accordingly, the focus is on the functional spaces of Malay vernacular houses to identify the vernacular features which can be utilized for the contemporary functional spaces. The analysis determines the vernacular architectural features of the functional spaces of Malay houses which represent the local needs. This study theorizes that the vernacular architectural features of functional spaces within Malay houses are influential in enhancing the quality of life. In conclusion, the Malay houses encompass profound vernacular features which can be considered in contemporary residential design for enhancing the Malay quality of life in urban area.